The Recreational Honda: A Didactic Sequence to Build a Bilingual Ecosystem Through Social Work in a Rural Community of Pereira (2022)
This paper presents a didactic sequence about bilingual recreational activities which will be carried out in La Honda, a rural community located in Combia-Baja Pereira Risaralda. The sequence will involve about 8 to10 students from 6 to 12 years old, whose English level is pre-A1. The main purpose of this didactic sequence is to generate social justice in terms of bilingual education for inhabitants of the community, with the objective to construct a bilingual ecosystem through workshops focused on recreational activities by designing lesson plans for the rural community, considering their real context, level of bilingual education, needs, and available resources. Some main concepts will be defined such as bilingual education, physical recreational activities, and Escuela Nueva. Additionally, important literature related to bilingual rural education will be reviewed to explore relevant findings from studies developed in similar contexts. Finally, the expected outcomes of this didactic sequence at the end of its implementation phase are focused on the English production of students related to vocabulary such as verbs and nouns associated with recreational activities and their English perception towards language chunks connected to body movements and commands.